Analisis Struktural Tari Sepen Penyok di Sanggar Kembang Kundor Desa Batu Penyu Kecamatan Gantung Kabupaten Belitung Timur - Miyah Agustina; Afifah Asriati (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This study aims to describe and analyze the movement structure of the Sepen Dentok Dance in the Kundor Flower Studio, Batu Penyu Village, Gantung District, East Belitung Regency. This research is a qualitative research. The object of the research is the Sepen Dentok Dance at the Kundor Flower Studio, Batu Penyu Village, Gantung District, East Belitung Regency. The types of data are primary data and secondary data. Supporting instruments used are stationery, and cameras. The steps of analyzing data are collecting data, describing the data and inferring the data. Data collection techniques are carried out through literature studies, observations, interviews, and documentation. The results of the study show that the relationship between the basic elements of the Sepen Penyok dance movement has basic elements related to the attitude and movement of the head, body, hands and feet. From the relationship system of the basic elements produce the forms of motifs. The hierarchical relationship system contained in the Sepen Penyok dance consists of 36 motifs, 15 phrases, 5 sentences, and 1 group. The Sepen Dentok Dance includes a syntagmatic relationship system, a relationship system that is like a link that cannot be separated or reversed between one and the other.